From classroom challenges to scholarly insights: a bibliometric analysis of novice teacher research - Yii, Beranda Ping Jin; Md Zalli, Mohd Muslim; Ahmi, Aidi; Law, Hui Haw; Benlahcene, Abderrahim; Mohd Jamil, Mohd Ridhuan; Quah, Wei Boon (John Wiley and Sons, 2025)
This study provides a comprehensive bibliometric analysis of research on novice teachers, drawing from the metadata of 1032 publications indexed in the Scopus database. It explores publication trends, key contributors and prevailing research themes from 1945 to 2024, offering insights to inform and enhance support systems for novice teachers. Data were analysed using tools such as Microsoft Excel, biblioMagika, OpenRefine, VOSviewer and Biblioshiny to evaluate publication metrics, collaboration patterns and thematic trends. The analysis reveals a steady publication growth over time, with the USA emerging as the most productive country, supported by key institutions such as the University of California and Harvard University. Teaching and Teacher Education is identified as the most influential journal in this field. Most of the novice teacher publications were written in English (94.86%) and focused on the fields of social sciences. Dominant themes include teacher development, professional practices, mentoring and identity formation. While relying on Scopus data, this study highlights the need to incorporate additional databases in future research to understand the evolving landscape comprehensively. By addressing literature gaps and emphasising emerging topics, this study contributes valuable insights to novice teacher research, offering implications for policy and practice in teacher education.